Treatment of complex coronary artery disease in patients with diabetes: 5-year results comparing outcomes of bypass surgery and percutaneous coronary intervention in the SYNTAX trial. - Kappetein, A; Head, S; Morice, M; Banning, A; Serruys, P; Mohr, F; Dawkins, K; Mack, M (2013)
OBJECTIVES: This prespecified subgroup analysis examined the effect of diabetes on left main coronary disease (LM) and/or three-vessel disease (3VD) in patients treated with percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) in the SYNTAX trial. METHODS: Patients (n = 1800) with LM and/or 3VD were randomized to receive either PCI with TAXUS Express paclitaxel-eluting stents or CABG. Five-year outcomes in subgroups with (n = 452) or without (n = 1348) diabetes were examined: major adverse cardiac or cerebrovascular events (MACCE), the composite safety end-point of all-cause death/stroke/myocardial infarction (MI) and individual MACCE components death, stroke, MI and repeat revascularization. Event rates were estimated with Kaplan-Meier analyses. RESULTS: In diabetic patients, 5-year rates were significantly higher for PCI vs CABG for MACCE (PCI: 46.5% vs CABG: 29.0%; P < 0.001) and repeat revascularization (PCI: 35.3% vs CABG: 14.6%; P < 0.001). There was no difference in the composite of all-cause death/stroke/MI (PCI: 23.9% vs CABG: 19.1%; P = 0.26) or individual components all-cause death (PCI: 19.5% vs CABG: 12.9%; P = 0.065), stroke (PCI: 3.0% vs CABG: 4.7%; P = 0.34) or MI (PCI: 9.0% vs CABG: 5.4%; P = 0.20). In non-diabetic patients, rates with PCI were also higher for MACCE (PCI: 34.1% vs CABG: 26.3%; P = 0.002) and repeat revascularization (PCI: 22.8% vs CABG: 13.4%; P < 0.001), but not for the composite end-point of all-cause death/stroke/MI (PCI: 19.8% vs CABG: 15.9%; P = 0.069). There were no differences in all-cause death (PCI: 12.0% vs CABG: 10.9%; P = 0.48) or stroke (PCI: 2.2% vs CABG: 3.5%; P = 0.15), but rates of MI (PCI: 9.9% vs CABG: 3.4%; P < 0.001) were significantly increased in the PCI arm in non-diabetic patients. CONCLUSIONS: In both diabetic and non-diabetic patients, PCI resulted in higher rates of MACCE and repeat revascularization at 5 years. Although PCI is a potential treatment option in patients with less-complex lesions, CABG should be the revascularization option of choice for patients with more-complex anatomic disease, especially with concurrent diabetes.